ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL DAUN YANG JATUH TAK PERNAH MEMBENCI ANGIN KARYA TERE LIYE - Nurmawati, Nurmawati (UNIB Press, 2016)
The purpose of this study to get an explanation on the description of the Analysis of character education Daun yang Jatuh Tak Pernah Membenci Angin Novel By Tere Liye. This research uses descriptive analysis method. descriptive analysis method used in this study means to obtain an accurate picture of the values of character education in novel Daun yang Jatuh Tak Pernah Membenci Angin Novel By Tere Liye. Technique Data collection was done by using the documentation that specifically examined the values of character education in novel Daun yang Jatuh Tak Pernah Membenci Angin Novel By Tere Liye. Based on the analysis of educational values contained in this novel there are as follows (1) relegius educational value such as prayer , grave pilgrimage , grateful (2) hard work as diligently and passionately in the work, (3) such as smart creative thinking and create the new things, (4) appreciate achievements such as awards to and achievement, (5) independent as not to depend on others, (6) curiosity such as asking questions, (7) friends / communicative as happy hanging out with other people, (8) social care such as giving comfort to those in need , and (9) responsibilities such as completing tasks without being asked or told.